First Record of Marine Dinofl agellate, Alexandrium tamutum (Dinophyceae) from Malaysia - Kon,, Nyuk Fong; Hii,, Kieng Soon; Tan,, Toh Hii; Yek,, Leh Hie; Lim,, Po Teen; Leaw,, Chui Pin (Malaysian Journal of Science, 2013)
Several species of dinofl agellates in the genus Alexandrium are known to be toxic, and have been associated with paralytic shellfi sh poisoning (PSP) in Malaysia. These Alexandrium species showed high morphological similarity among the toxic and non-toxic species, and detailed observation of the thecal plate’s arrangement is required for precise species identifi cation. Co-occurrence of the toxic and non-toxic species has complicated the plankton monitoring of PSP. In this study, a clone of Alexandrium species was established from plankton samples collected from Kota Belud, Sabah. The specimen was observed under epi-fl uorescence microscope, and nucleotide sequences of the nuclear-encoded ribosomal RNA gene obtained. Morphologically, the clone showed relatively wide and large sixth precingular plate (6´´) compared to that of A. minutum. The posterior sulcal plate (Sp) is similar to that of A. minutum, which is wider than long. The fi rst apical plate (1´) is irregularly rhomboidal with a small ventral pore (vp) present on its right margin. The morphological characters resembled to the species description of A. tamutum. Phylogenetic analysis of the ITS rDNA region also revealed a monophyly of this clone with other strains of A. tamutum, and separating them from the A. minutum clade. Species-specifi c sequence signatures of A. tamutum were obtained in silico, which could be as potential oligonucleotide probe regions for species detection by using molecular tool. This represents the fi rst report of A. tamutum found in Malaysian waters. (Keywords: Alexandrium tamutum, A. minutum, Sabah, Malaysia, thecal plates)